Relationship between Uric Acid Level and Hypertension Incidence in Takkalasi Village, Barru Regency - Sri Rahayu Jamaluddin; Andi Dhedie Prasatia Sam; Zulfahmidah; Irna Diyana Kartika; Abdul Mubdi Ardiansar Arifuddin Karim (Universitas Muhammadiyah Malang, 2025)
Introduction: Hypertension is one of the major risk factors for cardiovascular disease that causes high morbidity and mortality globally. The prevalence of hypertension continues to increase, including in Indonesia, including Barru Regency with a high incidence rate. One factor that is thought to play a role is high uric acid levels or hyperuricemia. Hyperuricemia can trigger activation of the renin-angiotensin-aldosterone system and oxidative stress, which contribute to increased blood pressure. Several studies have shown a close relationship between uric acid levels and the incidence of hypertension. Therefore, this study aims to analyze the relationship between uric acid levels and the incidence of hypertension in Takkalasi Village, Barru Regency. Methods: This type of research is a cross sectional study approach with a sampling technique, namely purposive sampling with a total of 23 samples each in the hyperuricemia group and non-hyperuricemia group so that the total sample is 46 samples. The research data is primary data taken directly in August - September 2024 in Takkalasi Village, Barru Regency which was then analyzed using the chi square test. Research Results: It was found that non-hyperuricemia respondents who suffered from hypertension were 21.7% and hyperuricemia sufferers who experienced hypertension were 32.6%. The chi square test that has been carried out shows a value of p=0.0139 (p>0.005). Conclusion: Uric acid levels are not significantly associated with hypertension. Even so, people are still asked to maintain a healthy lifestyle.